2004
DOI: 10.1002/jbm.b.30074
|View full text |Cite
|
Sign up to set email alerts
|

Leaching and mechanical properties characterization of dental composites

Abstract: The objective of this study was to determine the leaching of Ba, Si, and Sr from four dental composites: Restolux (RX), Micronew (M), Renew (RW), and Choice (C) and to correlate the effects of such leaching with flexure strength and modulus of elasticity. The specimens were 3 x 3 x 25-mm bars, polished with 120- and 240-grit SiC paper, and were aged for 4, 6, and 8 months in artificial saliva, distilled water, and a 50/50 mixture of ethanol and distilled water. Inductively coupled plasma with mass spectroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 8 publications
3
30
0
Order By: Relevance
“…[2][3][20][21][22] Some previous studies found that the release of particular filler particles, such as strontium or barium, were different after aging in ethanol, artificial saliva and distilled water. 4,[23][24] However, as only little correlation has been observed between filler leaching and flexural strength, Drummond and others assumed that the deterioration of dental composites is more closely related to degradation of the resin matrix and the matrix-filler bonds than degradation of the glass fillers, 25 which is in accordance with other reports. 20 Zhang reported that storage of specimens in a mixture of ethanol and water led to a significantly higher decrease in FS than did immersion in distilled water or artificial saliva.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…[2][3][20][21][22] Some previous studies found that the release of particular filler particles, such as strontium or barium, were different after aging in ethanol, artificial saliva and distilled water. 4,[23][24] However, as only little correlation has been observed between filler leaching and flexural strength, Drummond and others assumed that the deterioration of dental composites is more closely related to degradation of the resin matrix and the matrix-filler bonds than degradation of the glass fillers, 25 which is in accordance with other reports. 20 Zhang reported that storage of specimens in a mixture of ethanol and water led to a significantly higher decrease in FS than did immersion in distilled water or artificial saliva.…”
Section: Discussionsupporting
confidence: 68%
“…[4][5]8,16 With regard to this aspect, the findings of this in vitro study indicate that the aging medium has a negligible influence on mechanical performance, such as FS and VH. Generally, aging in aqueous solutions or the oral cavity may contribute to the leaching of composite components, degeneration of the cross-linked resin matrix and fostering hydrolysis of the filler-matrix interfaces.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Several studies demonstrated a significant influence of different aging media and aging times on the mechanical properties of resin-based composites [12,26,[40][41][42]. Hahnel and others demonstrated a significant effect of the composite materials and the storage times on the surface hardness and flexural strength; on the other hand Drummond showed a significant influence of the resin-composites and the storage media but not the storage times [18,40].…”
Section: Discussionmentioning
confidence: 99%
“…Their low filler loading indicates high resin contents which is based on UDMA and EBADMA. UDMA-based monomer system have shown less resistance to solvent degradation compared to the BIS-GMA-based materials [41,43]. Moreover, the increased plasticity of these bulk fill materials may led to the increased softening effect of the solvents [51].…”
Section: Discussionmentioning
confidence: 99%